The Effect of GDP per Capita, Corruption Perception Index, Human Development Index, and Coal Consumption on Carbon Dioxide Emissions in the BRICS Group of Countries - Daniel, Erikson; Nurjannah Rahayu Kistanti (Universitas Negeri Semarang, 2025)
Economic growth is an important indicator for a country's economy. Along with the development of economic activity, it also has an impact on the environment. This is discussed in the Environmental Kuznets Curve (EKC) theory where when per capita income increases, at a certain income level, environmental degradation also decreases. This study uses the Pooled Mean group/ARDL method from 1996 to 2021 in the BRICS country group. The results show that the EKC hypothesis does not hold in the short term, but holds in the long term. The corruption perception index has a positive and insignificant effect in the short term and a positive and significant effect in the long term, the human development index has a negative and insignificant effect in the short term and a negative and significant effect in the long term, finally coal consumption has a positive and significant effect in the short term and in the long term. Suggestions in this study include optimizing carbon taxes for countries that have not implemented them and making industrial business feasibility tests so that there are restrictions related to the waste produced.